2016
DOI: 10.3846/btp.2016.643
|View full text |Cite
|
Sign up to set email alerts
|

Model of Market Orientation of High-Tech Firms in Germany: Validation Study

Abstract: process of obtaining market information, its dissemina tion within the company and strategy implementation in response to the information obtained. The author of this study defines market orientation as a process of customer and competitor intelligence generation, intelligence dis semination and integration and responsiveness to mar ket intelligence. The shortened version of the instrument (MMOS) has been designed for practical reasons at the request of managers with company experience. The modi fied version a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the validity and reliability among latent-variables marketing-model and also the model should have the goodness of fitting the confirmatory factor analysis modeling that conducted to the measurement model and the structural equation modeling phase, entire the latent variables and its dimensions as the second order also the goodness of fit indexes modeling, as follow the table 3 below (Agostini, Nosella, & Filippini, 2016;Ghozali, 2013;Jangl, 2016 Furthermore, the definition operational of the entire latent variables determine within based on the SDL and GST-to an attain of the goal difficulty that the extent to which goal is challenging and requires and would lead the well mechanism that conducted within the Intellectual capital, digital technology quality, customer knowledge, value creation, and also the customer loyalty. (Landers et al, 2017;G.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the validity and reliability among latent-variables marketing-model and also the model should have the goodness of fitting the confirmatory factor analysis modeling that conducted to the measurement model and the structural equation modeling phase, entire the latent variables and its dimensions as the second order also the goodness of fit indexes modeling, as follow the table 3 below (Agostini, Nosella, & Filippini, 2016;Ghozali, 2013;Jangl, 2016 Furthermore, the definition operational of the entire latent variables determine within based on the SDL and GST-to an attain of the goal difficulty that the extent to which goal is challenging and requires and would lead the well mechanism that conducted within the Intellectual capital, digital technology quality, customer knowledge, value creation, and also the customer loyalty. (Landers et al, 2017;G.…”
Section: Methodsmentioning
confidence: 99%
“…In our opinion, however, we also find a good number of methodologically well-founded studies. Studying the modification procedures, we found that the research efforts are divided: some of them attempt to improve existing scales using purely quantitative procedures (Dawes 2000, Harrison and Walker 2001, Hajjat 2002 or based on the Cronbach's alpha index, which measures the reliability of scales or, with more advanced, multiple statistical techniques, using confirmatory factor analysis or structural equation modelling (Jangl 2016, Frösén et al 2016). Others logically focus on the literature or qualitative studies (in-depth interview, expert interview, focus group) (Oczkowski and Farrell 1997, Avlonitis and Gounaris 1999, Dawes 2000).…”
Section: Measurement Of Market Orientationmentioning
confidence: 99%
“…Moreover, the test of the validity and reliability of entire latent-variables analyzed and also the research-HR development model should have the goodness of fitting within the fitting-standard of SEM, the confirmatory factor analysis modeling that conducted to the measurement model and the structural equation modeling phase of the ordering, among the latent variables and its dimensions as the second order research-model and also the goodness of fit indexes modeling (Agostini, Nosella, & Filippini, 2016;Ghozali, 2013;Jangl, 2016;Susilo, 2020a) (Hair, Black, Babin andAnderson, 2010) (Evermann & Tate, 2016).…”
Section: An-employee Performance Within Industries Of Logisticshub Firmsmentioning
confidence: 99%